Sustainable Arabica coffee development strategies in Aceh, Indonesia. Issue 1 (February 2021) - Anhar, A; Rasyid, U H Ar; Muslih, A M; Baihaqi, A; Romano,; Abubakar, Y
Abstract: Arabica coffee is Aceh's leading commodity, apart from being an export product, it also plays an important role in the income of coffee farmers. Besides known as specialty coffee, Arabica coffee of Aceh has received international acknowledgment through several certifications, such as Fair Trade, Organic, or both, and other certificates. This study was conducted to develop sustainable development strategies for Arabica coffee of Aceh in the two largest coffee-producing districts, namely Bener Meriah and Aceh Tengah. Field study had been conducted from 1 December 2019 to 15 March 2020. Data were analysed by following the basic structure of the strengths, weaknesses, opportunities, and threats (SWOT) analysis. Sustainable arabica coffee can be carried out through implementing, monitoring, and evaluating policies related to coffee sustainability, increasing coffee productivity through climate-smart coffee practices, such as shade of coffee plantation, soil and water conservation, pest and disease control, development of new clones adapting to climate change, maintaining consistency of farmer's coffee quality, increasing coffee production by social forestry patterns mainly for coffee farmers who are currently in protected areas, and encouraging millennials to enter the coffee business (particularly in the upstream area).